Identification of Landslide Potential Area Based on UAV Data Analysis at Pidada Village Bandar Lampung City, Indonesia - Aldika Rizkiano; Muh Sarkowi; Rahmat Catur Wibowo (INSTEP Publishing Network, 2022)
Landslide is a natural disaster caused by activities or processes that disrupt the balance that causes the movement of soil and rock masses from high areas to low areas. To avoid high losses due to the disaster hazard, efforts are needed to minimize one of them by mapping areas of potential landslide disasters. This study aims to obtain the zone of potential landslide disaster area based on the data of slope class, rainfall and regional geology of the research area. The results of processing based on DTM (Digital Terrain Model) obtained slope classes, namely flat (0° – 2°) 19.36%, undulating slope (2° – 4°) 30.65%, undulating-rolling slope (4° – 8°) 19.72%, rolling-hilly slope (8° – 16°) 16, 4 %, hilly-steeply dissected slope (16° – 35°) 8.03%, steeply dissected-mountainous slope (35° – 55°) 4.58%, and mountainous slope (>55°) 1.27 %. Based on the analysis of slope class data, annual rainfall data and regional geological maps, there are potential landslide areas with areas marked with orange to red color symbols with a total area of ​​0.866 ha with hilly-steeply dissected slope (0.501 ha), steeply dissected-mountainous slope (0.286 ha) and mountainous slope (0.079 ha). The rainfall is 2800 – 3200 mm/year, and the regional geology is dominated by tuff.